THE RACK MECHANISM FOR DRIVING THE ACCESS FRAME IN A MULTI-STOREY ROBOTIC PARKING LOT ON DÂMBOVIȚA RIVER - Edward RĂȘCHITOR; Carmen Elisabeta RADU (Fiabilitate şi Durabilitate)
Considering the large number of cars, the necessity to build a robotic parking lot appeared. The work refers to the design of a mechanism with racks included in a robotic parking lot. For the access to the parking lot, a mechanism will be used that includes a shaft on which there are two engaging gears with two racks mounted on the vertical sides of the frame.